Opportunities and strategies for HIA implementation – from a public health perspective. (30th September 2020) - Mekel, O; Martin-Olmedo, P; Classen, T
Abstract: Health Impact Assessment (HIA) has various origins: environmental health, health promotion with the perspective of the wider determinants of health, and health equity. These three individual but related areas are linked by the overall aim of promoting healthier programmes, policies and projects, which are developed in non-health sectors mostly. As a consequence, this led to a significant use of HIA worldwide. The areas are complementary, but given their different original frameworks, applied methodologies may differ. Another typology of characterizing HIA can be done by the purpose for which HIA has been conducted in practice: mandated, decision support, advocacy and community-led HIA. These forms are important with regard to HIA implementation strategies. By now, the consideration of health in Environmental Impact Assessment (EIA) has become an established feature, not least due to the mandatory legal basis in many countries of the world. However, this situation is different for application in other policy areas so far. Some countries, in the absence of specific HIA legislation, have established HIA support units to conduct, commission, support HIA and deliver training. Advocacy and community-led HIA are mainly carried out by non-governmental organisations and universities. However, in general the potential of HIA has not yet been fully recognised: HIA is seen as a time-consuming and costly process and the effectiveness of HIA has not yet been communicated convincingly. The Health in All Policies approach is becoming increasingly important in the policy arena as a strategy to reduce non-communicable diseases by policies from non-health sectors. This requires different public health methods for implementation. HIA is particularly suitable for this. This development offers new opportunities for the implementation of HIA, which will be presented in detail.